PRESERVATION OF LIONG, ONE OF CHINESE PERANAKAN CULTURE IN HOO HAP HWEE, DAERAH ISTIMEWA YOGYAKARTA AS THE NEW-NORMAL CULTURAL TOURISM - Deni Dwi Ananti; Lenny Kurnia Octaviani; Dandi Erlangga (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Liong in Hoo Hap Hwee is one of the Chinese culture that has sustained in Yogyakarta. Liong is is a traditional dance and performance in the culture of Chinese society. Like the Lion or Barongsai Dance, this dance often appears at certain celebrations. The objectives of this research are to know role of Hoo Hap Hwee, the government, and cultural tourism in the preservation of Liong it self in adaptation era of new normal used a descriptive qualitative approach. The results showed that the preservation of Liong has been done and still run even though in this adaptation era of new normal. Hoo Hap Hwee and the government worked together to preserve the Liong by making adaptations such as holding online shows. In addition to adapting the show, training activities are also carried out with strict health protocols. Cultural tourism plays a big role in the preservation of the Liong at this time, the demand from cultural tourism makes the Liong one of the cultures that is also discussed in cultural activities such as online platforms, webinars and research.